A Homozygous RAB3GAP1:c.743delC Mutation in Rottweilers with Neuronal Vacuolation and Spinocerebellar Degeneration. (10th March 2016) - Mhlanga‐Mutangadura, T.; Johnson, G.S.; Ashwini, A.; Shelton, G.D.; Wennogle, S.A.; Johnson, G.C.; Kuroki, K.; O'Brien, D.P.
Abstract : Background: A variety of presumed hereditary, neurologic diseases have been reported in young Rottweilers. Overlapping ages of onset and clinical signs have made antemortem diagnosis difficult. One of these diseases, neuronal vacuolation and spinocerebellar degeneration (NVSD) shares clinical and histological features with polyneuropathy with ocular abnormalities and neuronal vacuolation (POANV), a recently described hereditary disease in Black Russian Terriers (BRTs). Dogs with POANV harbor mutations in RAB3GAP1 which codes for a protein involved in membrane trafficking. Hypothesis: Rottweilers with NVSD will be homozygous for the RAB3GAP1:c.743delC allele associated with POANV in BRTs. Animals: Eight Rottweilers with NVSD confirmed at necropsy, 128 Rottweilers without early onset neurologic signs, and 468 randomly selected dogs from 169 other breeds. Methods: Retrospective case–control study. Dogs were genotyped for the RAB3GAP1:c.743delC allele with an allelic discrimination assay. Results: All 8 NVSD‐affected dogs were homozygous for the RAB3GAP1:c.743delC allele while the 128 NVSD‐free Rottweilers were either homozygous for the reference allele (n = 105) or heterozygous (n = 23) and the 468 genotyped dogs from other breeds were all homozygous for the reference allele. Conclusions and Clinical Importance: The RAB3GAP1:c.743delC mutation is associated with a similar phenotype in Rottweilers and BRTs. Identification of the mutation permits a DNA test that can aid in the diagnosis of NVSD and identify carriers of the trait so that breeders can avoid producing affected dogs. Disruption of membrane trafficking could explain the neuronal vacuolation seen in NVSD and other spongiform encephalopathies.